DEVELOPMENT OF MATHEMATICS MATERIAL OF SET FOR GRADE VII STUDENT BASED ON CREATIVITY - Kharis Hudaiby Hanif; Harina Fitriyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Module limitation is one of the problems that affect the achievement of learning. The existing teaching materials are still challenging to understand. Teaching materials that can help students learn actively and independently are modules. This study aims to develop, test the feasibility of teaching materials in the form of modules, and know the student's response to developing mathematics materials based on creativity. This type of research is research development. The development procedure steps are potentials and problems, data collection, product design, design validation, product testing, product revision, and trial usage. Research subjects were material experts, media experts, and student response in SMP Muhammadiyah Boarding School (MBS) Pleret and Junior High School (SMP), Muhammadiyah Sanden. This research object is the subject matter of Mathematics Material of Set for VII Student Based on Creativity. Data collection techniques in this study are by using questionnaires. The results showed that the average material scores 80,33 were excellent; the average media scores 85,33 with the excellent category and the average student response rating of 73,33 with the excellent category. Based on these calculations' results, the mathematical material in the form of modules developed feasible to use in learning mathematics.